The formation of job referral networks: Experimental evidence from urban Ethiopia - Caria, Antonia Stefano; Hassen, Ibrahim Worku (International Food Policy Research Institute, 2013)
In this study we focus on exclusion from job contact networks, which constitutes a major disadvantage for labor market participants in settings where referral hiring is common and information about jobs hard to obtain. In a mid-size town in northern Ethiopia, where these mechanisms are at work, we observe that many individuals do not access local job contact networks. Models of strategic network formation and behavioral decision theory suggest that given the right incentives, job contact networks should be more inclusive. On these grounds we hypothesize that workers would link to peripheral peers when this maximizes their chances of referral and when self-regarding concerns are absent due to social preferences.